Cross-cultural social media marketing : bridging across cultural differences - Moriuchi, Emi (Emerald points., 2021)
To increase brand awareness, engagement and revenue, companies are acknowledging the importance of integrating social media marketing in their overall marketing strategy. Social media marketing complements a brand or company's current marketing strategy as it aids in amplifying a company's brand voice and presence. This book consists of a step-by-step guide in using social media successfully in an ever-growing consumer market, domestically and internationally. Marketers must be strategic in how they utilize these platforms by first understanding their consumers, while at the same time, meeting their business goals and objectives. Case studies on companies that use social media and advanced technologies to increase their brand awareness, engagement and conversion are discussed in this book. As businesses globalize, many marketers are struggling to establish a presence outside of the United States. Thus, this book also discusses the cultural differences in each country and how these differences matter when considering the usage of each of the social media platforms in certain countries. In this new work, digital marketing expert Emi Moriuchi educates business owners, marketing practitioners, students, as well as marketing researchers in understanding the usage of social media strategy . Containing both evergreen content as well as trending knowledge in the consumer market, this is a must-read for understanding social media marketing for domestic and international market.